Process intensification in wastewater treatment: Oxygen transfer characterisation of a jet loop reactor for aerobic biological wastewater treatment - Keskinler, B.; Akay, G.; Pekdemir, T.; Yildiz, E.; Nuhoglu, A. (Inderscience Publishers, 2004)
The overall volumetric mass transfer coefficient (KLa) and the overall gas holdup (?) were measured in a jet loop reactor (JLR) used for the intensive aerobic biological treatment of waste water. The process parameters and their ranges were: inlet water flow rate: 30 ? QL ? 70 l/min, inlet air flow rate: 4 ? Qg ? 36 l/min. The ratio of water flow rates from the bottom of the reactor (QB) and the inlet water flow rate (QL) varied in the range 0.0 ? Q B/QL ? 0.92. It was found that, both KLa, and ? increased with increasing Qg. Up to a critical Q g value, neither KLa nor ? varied with energy dissipation rate per unit volume, E/V, but beyond these Qg values, KLa decreased while ? increased with increasing E/V. Water withdrawal from the bottom of the reactor in addition to that from the top, increased KLa up to 30% depending on the process conditions. Use of pure oxygen instead of air could also lead to increases in KLa up to 19%.
Keywords: Gas hold-up; Jet loop reactor; Mass transfer; Oxygen transfer; Process intensification; Waste water; Water treatment